MYH9 related disease : a novel missense Ala95Asp mutation of the MYH9 gene - de Rocco, Daniela (2009)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephritis leading to end-stage renal failure. In a family with eight individuals suffering from macrothrombocytopenia and hearing impairment we identified a novel c.Ala95Asp mutation. Affecting the motor domain of the protein, the mutation is likely to be associated with a severe phenotype. Therefore, this family should be carefully monitored to follow-up the renal status even though the affected members do not seem to be at risk of early kidney disease.